PELAKSANAAN JAMINAN KESEHATAN BAGI MASYARAKAT MISKIN DI JORONG TONGAR NAGARI AIA GADANG KABUPATEN PASAMAN BARAT. - Putri, Anike - (Pendidikan Sosiologi, 2014)
Jamkesmas is a social assistance program for health care for the poor and not capable of being conducted nationally, to enable the cross-subsidy in order to realize comprehensive healthcare services for the poor. The purpose of this program is to improve access and quality of health services to all poor and can not afford in order to achieve optimal health status effectively and efficiently. However, in the implementation jamkesmas in Jorong Tongar imbalance occurs, so that the formulation of the problem in this research is to what extent the implementation of the inequality of health insurance for the poor in Jorong Tongar and how the impact of inequality in the implementation of health insurance in Jorong Tongar. The purpose of this study was to describe the causes of inequality jamkesmas implementation, and describe the impact of the implementation jamkesmas inequality for the poor in Jorong Tongar Nagari Aia Pasaman West Tower. The method in this study using qualitative methods. The technique used for data collection are observation, interview and documentation. Informants in this study are set intentionally (purposive sampling), the number of informants are all 20, 10 and 5 beneficiary communities jamkesmas officers, employees and 5 Department of Health or the person in charge of the implementation. Based on the results of the study revealed that there are three factors that cause imbalance in the implementation of health insurance Jorong Nagari Tongar Aia Tower namely: 1). System improper procedure, 2). Inaccurate data collection, 3). A system of bribes from the local community, while the impact of the imbalance in the implementation of health insurance programs, namely: 1). The lack of public confidence in the officers jamkesmas, 2). Social tension, it can be concluded as follows: type of public health programs is poor in Jorong Tongar medical treatment. Most of the people belonging to the community Jorong Tongar incapable of about 761 people who were supposed to get Jamkemas for treatment to nearby hospitals and health centers. Of the 761 persons only 125 people get in Jorong Tongar.